HYDROTREATING AND HYDROISOMERIZATION OF OIL FRACTIONS ON MODIFIED ALUMINUM-COBALTMOLYBDENUM CATALYSTS - Tuktin B.T.; Shapovalova L.B.; Tenizbayeva A.A; Abilmagzhanov A.Z.; Egizbaeva R.I. (Academic Scientific Journal of Chemistry, 2020)
In this work we are given results and research of hydro refining of gasoline and diesel oil fractions on alumina catalysts CoO-MoO3-La2О3-Р2О5-ZSM-Al2O3, CoO-MoO3-Ce2О3-Р2О5-ZSM-HY-Al2O3, CoO-MoO3- La2О3-Р2О5- AAC-ZSM -Al2O3. The catalysts were prepared by impregnating a mixture of aluminum hydroxide and zeolites ZSM-5, HY with aqueous solutions of salts Co, Mo, La and phosphoric acid. Large-scale laboratory tests of the synthesized catalysts were carried out in the process of hydro processing of various types of gasoline and diesel fractions. At hydro treating of straight-run gasoline over CoO-MoO3-La2О3-Р2О5-ZSM-Al2O3 shows that in the temperature range 320 - 350о С the maximum amount of isoalkanes is formed 33.4-40.4%. The octane number of refined gasoline increases in comparison with the initial one from 78.9 to 89.3 (RON) and from 60.9 to 73.4 (MON). The sulfur content of catalysate with increasing temperature up to 400о С decreased to 0.0012 %. At hydro processing of catalytic cracking gasoline on CoO-MoO3-La2О3-Р2О5-ZSM-Al2O3 the octane number of refined gasoline is slightly reduced. The sulfur content of catalysate with increasing temperature up to 400о С decreased from initial with from 0.0134 to 0 0014 %. It was found that the lowest pour point and cloud point of hydro-refined diesel fuel is observed on the catalyst CoO-MoO3-La2O3-P2O5-ZSM-Al2O3. After hydro treating on this catalyst the pour point and cloud point are equal to minus 52.7o C and minus 40.8o C accordingly. This same catalyst has the highest hydro desulfurization activity: the sulfur content decreases from 0.5600% to 0.104%. Thus, the developed modified zeolite-containing catalysts CoO-MoO3-La2О3-P2O5-ZSM-Al2O3, CoO-MoO3- Се2О3-P2O5-ZSM-HY-Al2O3, CoO-MoO3-La2О3-P2O5-AAC-ZSM-Al2O3, exhibiting high activity at hydro treating of gasoline and diesel fractions and is able in one stage deep hydro treating, hydro isomerization and hydrocracking which allows to obtain low-sulfur, high-octane gasoline and low-sulfur and low solidifying diesel fuel which is important for operation of vehicles in winter conditions.